Supplementary Feeding: Effect on Growth and Blood Metabolites in Sahiwal Heifers - Narvariya, D.S.; Chandra, Ramesh; Kumar, Nishant; Roy, A.K.; Datt, Chander; Mehla, R.K. (Indian Journal of Animal Nutrition, 2018)
The present study was conducted to evaluate the effect of provision of 25% extra concentrate mixture over and above the NRC recommendation on body growth and blood metabolite levels in Sahiwal heifers. The average daily body weight gain was higher (P